Re-Panning of Directional Signals and its Impact on Localization - Adami, Alexander; Schöffler, Michael; Herre, Jürgen (2015 23rd European Signal Processing Conference, EUSIPCO 2015, 2015)
For multichannel audio reproduction systems, it is crucial to set up the speakers correctly according to the multichannel format's specification. Especially, the predefined angle of every speaker with respect to the listening position must be strictly kept to avoid spatial distortions of virtual sources, the so called phantom sources. In a normal living room environment, a specification compliant setup is usually not possible. This means, the resulting audio scene may differ heavily from the originally intended scene, i.e., the phantom sources' positions change. To mitigate these spatial distortions, we propose a re-panning method of directional signals. The method groups pairs of adjacent loudspeakers into segments, analyses the direction of arrivals (DOAs) within each segment by means of a direct-ambience decomposition and re-renders the direct components with respect to the actual reproduction setup. The re-panning method was perceptually evaluated by means of a localization listening test.
Vorträge und Veröffentlichungen auf Konferenzen_Subjektive Audioqualität
Keywords: format conversion; localization; Spatial audio